Unsheltered eaudiobook A novel. - Kingsolver, Barbara (2018)
New York Times Bestseller Named one of the Best Books of the Year by NPR, O: The Oprah Magazine, San Francisco Chronicle , Christian Science Monitor and Newsweek "Kingsolver brilliantly captures both the price of profound change and how it can pave the way not only for future generations, but also for a radiant, unexpected expansion of the heart." — O: The Oprah Magazine The acclaimed author of The Poisonwood Bible and The Bean Trees, and recipient of numerous literary awards—including the National Humanities Medal, the Dayton Literary Peace Prize, and the National Book Foundation's Medal for Distinguish Contribution to American Letters—returns with a story about two families, in two centuries, navigating what seems to be the end of the world as they know it. With history as their tantalizing canvas, these characters paint a startlingly relevant portrait of life in precarious times when the foundations of the past have failed to prepare us for the future. How could two hardworking people do everything right in life, a woman asks, and end up destitute? Willa Knox and her husband followed all the rules as responsible parents and professionals, and have nothing to show for it but debts and an inherited brick house that is falling apart. The magazine where Willa worked has folded; the college where her husband had tenure has closed. Their dubious shelter is also the only option for a disabled father-in-law and an exasperating, free-spirited daughter. When the family's one success story, an Ivy-educated son, is uprooted by tragedy he seems likely to join them, with dark complications of his own. In another time, a troubled husband and public servant asks, How can a man tell the truth, and be reviled for it? A science teacher with a passion for honest investigation, Thatcher Greenwood finds himself under siege: his employer forbids him to speak of the exciting work just published by Charles Darwin. His young bride and social-climbing mother-in-law bristle at the risk of scandal, and dismiss his worries that their elegant house is unsound. In a village ostensibly founded as a benevolent Utopia, Thatcher wants only to honor his duties, but his friendships with a woman scientist and a renegade newspaper editor threaten to draw him into a vendetta with the town's powerful men. A timely and ""utterly captivating"" novel (San Francisco Chronicle), Unsheltered interweaves past and present to explore the human capacity for resiliency and compassion in times of great upheaval.